(untitled) (Web of Teachers: Inderscience Research, 2026)
The article reveals the essence of the theory of labor education in Kazakh folk pedagogy, its goals and objectives, its content and structural components, and its practical mechanisms. Based on folk experience, the influence of labor on personality formation is analyzed, as well as the role of the family, community, and the traditional way of life in cultivating diligence, responsibility, honesty, patience, and vocational orientation. Proverbs and sayings, tales and legends, customs, the mentorship tradition (“ustaz–shogird”), and everyday labor practice are also examined as the main means of labor education. The study substantiates labor education as an interconnected system of educational (moral), social, and professional directions; practical ways of integrating it into the modern educational process are proposed (project-based activities, life skills, career guidance, socially useful labor).